Exploiting landrace genetic diversity for germplasm enhancement in durum wheat breeding in Morocco - Taghouti M.; Rhrib K.; Gaboun F. (Proceedings of the International Symposium on Genetics and breeding of durum wheat, 2014)
Traditional durum wheat farming communities have contributed for centuries to the evolution and enrichment of on-farm conservation of diverse wheat landraces, and to the development of farmer’s seed exchange in order to ensure the continued evolution and diversification of these landraces especially under dry growing conditions. Landraces are genetically heterogeneous and have over many generations become adapted to the local environment and cultural conditions under which they are grown. However, during the last century, the introduction of high-yielding varieties, and the structural changes in wheat farming systems, led to the loss of genetic diversity of wheat landraces. In Morocco, landraces of durum wheat are still cultivated by farmers especially in marginal regions such as mountains and Saharan areas. Durum wheat landraces are highly appreciated for their adaptation to some abiotic stresses and mainly for their good grain and straw qualities. This paper summarizes some studies aiming to assess the amount of diversity of Moroccan landraces collected in two different agro-ecological areas of Morocco, and determine options for adding the value of these landraces. The evaluation of these landraces focused on agro morphological characters and specific quality parameters. The results showed a large genetic variability in this germplasm proving the possibility of using landraces as promising genepool in breeding program especially for improving grain quality. The results indicated also the possibility of improving on farm landraces productivity through “composite landraces” approach and low cost agricultural packages.
International Symposium : Genetics and Breeding of Durum Wheat, 2013/05/27-30, Rome (Italy)